Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF

Developing techno-economically sustainable methodologies for deep desulfurization using hydrodynamic cavitation - Suryawanshi, N.B. (Fuel, 2017)
The present work, for the first time, describes the efficacy of the cavitation process and compares the cavitation yield for two types of cavitation devices-one employing linear flow for the generation of cavities and other employing vortex flow. The process involves pre-programmed mixing of the organic and aqueous phases, and can be carried out using simple mechanical cavitating devices such as orifice or vortex diode. The process essentially exploits in situ generation of oxidising agents such as hydroxyl radicals for oxidative removal of sulfur. The efficiency of the process is strongly dependent on the nature of device apart from the nature of the organic phase. The effects of process parameters and engineering designs were established for three organic solvents (n-octane, toluene, n-octanol) for model sulfur compound-Thiophene. A very high removal to the extent of 95% was demonstrated. The results were also verified using commercial diesel. The cavitation yield is significantly higher for vortex diode compared to the orifice. The process has potential to provide a green approach for desulfurization of fuels or organics without the use of catalyst or external chemicals/reagents apart from newer engineering configurations for effective implementation of hydrodynamic cavitation in industrial practice and also appears to be economically sustainable.
Keywords: Fuel; Oxidation; Petroleum; Pollution Control; Sulphur Removal

Drying of almonds I: single particle - Chilka, A. G.; Ranade, V. V. (Indian Chemical Engineer, 2017)
Drying is an essential unit operation required in food processing industries, particularly in the dry fruits industry. Drying of almonds exhibit many characteristic features such as non-spherical shape, swelling/ shrinkage as a function of moisture content, uneven drying because of their peculiar shape and proximity to other almond kernels and so on. In this study, we have investigated the drying of almonds through experiments and computational modelling. In this regard, Mettler Toledo Halogen moisture analyzer unit was used to conduct experiments for a single almond kernel. In this widely used equipment, internal air flow patterns and therefore heat and mass transfer depend on natural circulation of air. A detailed three-dimensional computational fluid dynamics (CFD) model was used to simulate the air flow pattern, heat and mass transfer in the drying unit. Carefully designed experiments with a single almond kernel were carried out at different temperatures to estimate key parameters of interest (drying kinetics and effective diffusivity). The CFD model was also used to quantify non-uniform heat and mass transfer and therefore non-uniform drying of a single almond kernel. The presented approach, models and results might be useful to improve the performance of drying units in industrial systems. The results and models presented here will also provide a basis for further work on multiple almond kernels and on tray dryer unit. © 2017 Indian Institute of Chemical Engineers

Drying of almonds II: multiple particles - Chilka, A. G. (Indian Chemical Engineer, 2017)
Computational modelling is an efficient and effective tool for modelling the drying process for food products. Developing validated computational models for drying processes is essential to build energy-efficient drying units, producing uniform quality of dried products. This work presents drying behaviour of almonds with a specific focus on understanding interaction among multiple almonds. Eight (2 × 2 × 2) particles and twenty seven (3 × 3 × 3) particles arranged in the shape of a cuboid were used to conduct drying experiments in a Mettler Toledo Moisture Analyzer unit. Experiments were conducted to measure the moisture loss data with respect to drying time using almond kernels. Experimental data were used to understand drying kinetics as well as variation in moisture content with respect to their positions in a cuboid. Computational fluid dynamics based simulations were carried out for the flow, heat transfer and drying of particles in the unit. Actual geometry of individual particles was considered in simulations to predict the variation in velocity, heat and mass transfer coefficients for all the particles. Simulations predicted moisture loss data that matches well with the experimentally measured values. Average moisture for each layer was also compared for various intermediate drying times. Simulation results captured the overall drying process for multiple particles system adequately. The results are compared with the results obtained with drying of a single almond. The approach, models and presented results will be useful for designing large-scale drying units for almonds. © 2017 Indian Institute of Chemical Engineers
Keywords: Almonds; CFD; Drying